Legal Service Agencies, 1970 - Champagne, Anthony S. ([Verlag nicht ermittelbar], 1984)
These data, focusing on the effectiveness of legal service programs, were collected by the Office of Legal Services under the Office of Economic Opportunity. The data include information about each agency, its budget, and the characteristics of its clients and personnel. Evaluations of the agency's effectiveness and operation were made by a visiting observer based on consultations with staff and community members. Evaluative measures include community attitudes, agency resources, and staff competence.